Red angel - Arima, Yorichika 1918-1980; Ikeno, Sei 1931-2004 (Arrow Films, 2022)
"During the Sino-Japanese War, a young army nurse gives sympathy to her patients and falls in love with an impotent doctor who's addicted to morphine." [imdb.com]
Original: Japan 1966
Special edition contents: High Definition Blu-ray ; original uncompressed Japanese mono audio ; optional English subtitles ; brand new audio commentary by Japanese cinema scholar David Desser ; newly filmed introduction by Japanese cinema expert Tony Rayns ; 'Not all angels have wings,' a new video essay by film critic Jonathan Rosenbaum ; original trailers ; image gallery ; reversible sleeve featuring original and newly commissioned artwork by Tony Stella
Bildformat 2.35:1
Keywords: Film; Blu-Ray-Disc